Reimagining HR for better well-being and performance - Kellerman, Gabriella Rosen; Seligman, Martin (MIT Sloan Management Review, 2023)
This article, adapted from the new book Tomorrowmind, looks at how having siloed HR functions hinders the development and implementation of programs that could better support employee mental health and thriving. The authors discuss four hurdles that make it difficult to proactively prevent the onset of physical or psychological health issues and suggest ways that Benefits and L&D teams can work together to execute effective interventions to mitigate workplace stressors.